Assessing the Roles of Network Structure and Social Media in Inter-units Knowledge Sharing - Sayogo, Djoko Sigit; Yuli, Sri Budi Cantika; Suliswanto, Muhammad Sri Wahyudi; Affan, Wildan (Journal of Innovation in Business and Economics, 2018)
Sharing knowledge across different units within an organization can be considered as one of the organization’s fundamental operation. Nonetheless, sharing information and knowledge across boundaries presents tremendous challenges for organization. This paper discusses the impact of social network structure and social media in mediating knowledge sharing against unit task performance. Based on the review of extant literatures in intra-organization information and knowlegde sharing, this paper accentuates on three propositions as follows: a) the use of online collaborative media reduces time spend on task by accelerating the electronic document quality assurance process, b) integrating expert ability with the use of collaborative media reduces time spend on task by accelerating the electronic document quality assurance process, and c) social network structure increase the likelihood to extract personal advice from colleagues, thus improve unit’s work quality.